Climate warming and extended droughts drive establishment and growth dynamics in temperate grassland plants - Doležal, Jiří; Altman, Jan; Jandová, Veronika; Chytrý, Milan; Conti, Luisa; Méndez-Castro, Francisco E.; Klimešová, Jitka; Zelený, David; Ottaviani, Gianluigi (Agricultural and forest meteorology, 2022)
•Central European grassland plants record climate changes in their radial growth rings.•Warmer and drier climate reduces plant growth and establishment.•Summer droughts adversely affect mainly the growth of shallow-rooted species.•Growth responses over the past thirty years were species-specific and related to life histories.•Herb-chronology provides in-depth insights into climate effects on plant fitness. Current climate warming and extended droughts have major impacts on plant performance, with consequences for biodiversity and ecosystem functioning. However, unlike in trees, little is known about species-specific responses in grassland plants and the role of their different life histories in mitigating climate change impacts. We studied the climate-related plant establishment and growth dynamics over the last thirty years in four Central European grassland species with contrasting rooting depth, seed mass and xylem anatomy, and hence ability to cope with drought-induced restriction on establishment and growth. To assess the annual and seasonal dependency on fluctuating temperature and precipitation, we reconstructed establishment and growth chronologies from 174 individuals spanning 1–29 years, and more than 2,500 annual growth increments. We identified contrasting climatic controls of establishment and growth among focal species, which were likely related to their different traits. The establishment of deep-rooted, heavy-seeded species profited from increased winter and early spring precipitation, while the establishment of shallow-rooted, light-seeded species was weakly influenced by climate fluctuations. However, their growth was more adversely affected by high summer temperatures and drought than the growth of deep-rooted species. Our results show that the change towards a warmer and drier climate over the past thirty years profoundly reduced the growth and establishment of studied grassland plants. Most individuals established in the wet period of the 2000s, but the establishment reduced considerably during the dry and warm period of the 2010s. Our results provide novel insights into species-specific climate dependency of plant establishment, growth and population dynamics, suggesting the high vulnerability of Central European grasslands to climate warming. [Display omitted]